2018
DOI: 10.1192/bjo.2017.3
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic variations regarding clinical profiles and symptom representation in prisoners with psychotic disorders

Abstract: BackgroundBlack and minority ethnic (BME) groups are known to have higher prevalences of psychotic disorders and are over-represented in western penitentiaries and forensic psychiatric institutions. Research from regular mental healthcare settings suggests that they could show different and more severe psychotic symptoms.AimsTo explore ethnic variations in severity of symptomatology of BME and non-BME detainees with psychotic disorders.MethodIn this study, 824 patients with psychotic disorders from seven diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
(80 reference statements)
1
4
0
Order By: Relevance
“…Forensic patients with psychiatric disorders showed various neuropsychological impairments, mainly related to memory, cognition and impulsivity, which can increase the risk of violent behavior [52][53][54][55][56] . This fact matches the literature in that it affirms the importance of neuropsychological assessment of psychiatric and neurological patients, as it can provide important information about risk factors, deficits or associated dysfunctions 57,58 .…”
Section: In the Forensic Context Neuropsychological Assessment Is Com...supporting
confidence: 86%
“…Forensic patients with psychiatric disorders showed various neuropsychological impairments, mainly related to memory, cognition and impulsivity, which can increase the risk of violent behavior [52][53][54][55][56] . This fact matches the literature in that it affirms the importance of neuropsychological assessment of psychiatric and neurological patients, as it can provide important information about risk factors, deficits or associated dysfunctions 57,58 .…”
Section: In the Forensic Context Neuropsychological Assessment Is Com...supporting
confidence: 86%
“…Some studies have found that forensic patients are more likely to be diagnosed with psychotic disorders, including SSD, if they have a migrant or ethnic minority background [24,27,28]. In this context, the role of ethnic variations in symptomatology of SSD remains to be clarified [29,30]. Cultural and linguistic differences between ethnic minority patients and mental health professionals have been reported to complicate diagnostic and therapeutic practice in both general and forensic psychiatry [10,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Due to rising immigration in recent years, cultural influences on mental health and delinquency are increasingly gaining in significance. Enhancing public and prison health care should not only be seen as a political duty; being responsive to the requirements of different minority groups also involves promoting the process of social integration, maintaining mental health, and preventing the aggravation of psychiatric symptoms (22,72,73).…”
Section: Resultsmentioning
confidence: 99%